(3GJLGgGJ UMa MRH GdhaO hGdgjFI GdSYOjI hGdcJdI GdhaOjI fMh bVGjG GdeLJeY GdeUQi GdSjGSjI hGdGLJeGYjI (B1936 - 1953: s (3OQGSI JMdjdjI ebGQfI (B/ s - (3eMeO TYHGf MSf eHQhc s; (3YhGWa YHOGdQMef (B: s ((3GdbGgQI (B: s (3eMeO TYHGf MSf eHQhc (B: s, 2011)
(3GSJgOaJ GdOQGSI QUO hJMdjd hebGQfI GJLGgGJ UMa MRH GdhaO hGdgjFI GdSYOjI hGdcJdI GdhaOjI fMh bVGjG GdeLJeY GdeUQi GdSjGSjI hGdGLJeGYjI hgi (B( (3GdLdGA hhMOI hGOi Gdfjd hGdOSJhQ (B- (3GdJYdje hGdeQCI hGdYOGdI GdGLJeGYjI (B) (3ajeG Hjf YGei (B( 1936 - 1953 ) (3hPdc ddcTa Yf GdOhQ GdPi bGeJ Hg Jdc GdUMa ai EOGQI GdUQGYGJ GdMRHjI ai Jdc GdaJQI ceG GSJgOaJ GdOQGSI GdcTa Yf eXGgQ JYHjQ GdUMa eMd GdOQGSI Yf gPg GdCMRGH hJaSjQ CSHGH GdGNJdGa Ch GdGJaGb Hjf GJLGgGJ gPg GdUMa GdeNJdaIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEYdGe (B- (3bSe GdUMGaIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3UMGaI GdcJdI GdhaOjI s; (3UMGaI GdgjFI GdSYOjI s; (3UMGaI GdhaO s